Biomimetic polypeptoids with para-oligo(ethylene glycol) benzyl side-chains synthesized from α-Amino acids. (October 2019) - Fu, Xiaohui; Li, Zheng; Lin, Min; Sun, Jing; Li, Zhibo
Graphical abstract: Highlights: Synthesis of oligopeptoids with para-oligo(ethylene glycol) benzyl side-chains. Thermo-induced aggregation behaviors in water. The oligopeptoids display low cytotoxicity toward HeLa cells. Abstract: A series of N -alkylated glycine andl -alanine bearing oligoethylene glycol (OEG) and benzyl side chains, i.e., N -(4-oligoethylene glycol)benzyl glycine and N -(4-oligoethylene glycol)benzyl alanine (NMe(OEt)x OBnG and NMe(OEt)x OBnA, x = 1–3), have been readily synthesized via schiff base and reductive amination reactions. The successful ring opening polymerization (ROP) of N -substituted glycine N -carboxyanhydrides (NCA) results in three types of peptoid oligomers (PNMe(OEt)x OBnG, x = 1–3). Depending on the length of OEG side chains, PNMe(OEt)x OBnG show different solubility in water. Particularly, the as-prepared oligomers containing three ethylene glycol units (PNMe(OEt)3 OBnG) display interesting thermoresponsive aggregation behaviors in water. DSC results reveal that all the oligomers show crystalline behaviors with melting temperatures decreasing as the OEG side chain length is increased. Both live-dead and MTT assays indicate low cytotoxicity of PNMe(OEt)2 OBnG and PNMe(OEt)3 OBnG toward HeLa cells, comparable to benchmark PEG. Concerning thermoresponsive and crystalline properties, the as-prepared peptoid oligomers are potentially promising building blocks for stimuli-responsive bioinspired materials and hierarchical self-assembly.